2021
DOI: 10.1002/smtd.202100115
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Tadalafil Nanovaccine for Cancer Immunotherapy by Alleviating Myeloid‐Derived Suppressor Cells and Heightening Immunogenicity

Abstract: Tumor‐induced immune suppression mediated by myeloid‐derived suppressor cells (MDSCs) and insufficient immunogenicity are two major factors for the poor overall response rate to the immune checkpoint blockade (ICB). Here, a tumor microenvironment responsive nanoprodrug (FIT nanoparticles) is presented for co‐delivering tadalafil (TAD) and indocyanine green (ICG) photosensitizer to simultaneously targeting intratumor MDSCs and amplifying tumor immunogenicity. The resulting nanoprodrug shows high drug loading (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…Nevertheless, co-administration therapy may also have additive or synergistic effects resulted from interaction with several distinct targets at reduced administrated doses (Eftekhari et al., 2019 ). At present, there have been studies on nano-drug delivery system (NDDS) for the co-delivery of chemotherapy drugs with photosensitizers (Xiao et al., 2021 ; Zhang et al., 2021b ), and natural active ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, co-administration therapy may also have additive or synergistic effects resulted from interaction with several distinct targets at reduced administrated doses (Eftekhari et al., 2019 ). At present, there have been studies on nano-drug delivery system (NDDS) for the co-delivery of chemotherapy drugs with photosensitizers (Xiao et al., 2021 ; Zhang et al., 2021b ), and natural active ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…These nanovaccines can also be used in combination with other therapeutic approaches such as radiotherapy, immunotherapy, and chemotherapy, and by synergizing anti-tumor responses, they can eliminate the tumor, inhibit metastasis, and increase survival. According to this review of the latest studies on nanovaccines in cancer therapy, it is essential to comprehensively elucidate the mechanism of action of this nanovaccine [ 113 ]. Correspondingly, nanovaccine safety should be studied systematically.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, FIT + L could markedly suppress tumor growth without changing the studied mice’s weight. The authors suggested that these occurrences lead to DCs’ maturation and T cell activation, strengthening the anti-tumor immune response and immune checkpoint blockade efficacy [ 113 ].…”
Section: Nanovaccines In Cancer Therapymentioning
confidence: 99%
“…In this regard, Duranti, Ceci, et al (2021) and Duranti, Maldini, et al (2021) demonstrate that Tadalafil improved oxidative capacity in C2C12 skeletal muscle cells by enhancing fat metabolism. As oxidation of the fatty acids needs more oxygen than glucose oxidation, elevated oxygen consumption in mitochondrial increases formation of the ROS (Zhang et al, 2021). Glutathione is the primary antioxidant responsible for maintaining a reduced intracellular microenvironment, and Tadalafil administration produced a redox perturbation by the altered GSH/GSSG ratio with no effect on TAS (Duranti, Ceci, et al, 2021; Duranti, Maldini, et al, 2021) which our findings were in agreement to this report.…”
Section: Discussionmentioning
confidence: 99%